(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This study undertakes a comparative analysis of the semantic fields of distress, specifically focusing on expressions of sorrow and grief, as manifested in selected literary excerpts from William Shakespeare’s Othello and Maksud Shaykhzoda’s Mirzo Ulugbek. Employing a corpus-assisted discourse analysis approach, this research investigates the collocational patterns and semantic prosody associated with key lexical items denoting sorrow in both English and Uzbek. The aim is to identify both universal and culture-specific linguistic mechanisms through which these profound emotions are articulated and understood within their respective literary and cultural contexts. Drawing upon theories of semantic fields and semantic prosody, this study examines the immediate linguistic environment of core sorrow-related terms in both source texts. Collocational analysis reveals the typical co-occurrence of words, shedding light on the semantic associations and conceptual frameworks surrounding sorrow in each language. For instance, the study explores whether “sorrow” in Othello frequently collocates with terms of despair, tears, or loss, and how these patterns compare with the collocates of Uzbek equivalents such as “gʻam”, “alam”, or “qaygʻu” in Mirzo Ulugbek, potentially revealing differences in the perceived intensity, manifestation, or consequences of sorrow.